Artichoke for biochemistry, histology, and gene expression in obstructive jaundice - Celepli,Salih (2022)
SUMMARY OBJECTIVE: This study aimed to evaluate the hepatoprotective effect of artichoke leaf extract (Cynara scolymus) in experimental obstructive jaundice. METHODS: Rats were separated into three groups, namely, sham, control, and artichoke leaf extract. Ischemia was created for 60 min, and then liver tissue and blood samples were taken at the 90th minute of reperfusion. Artichoke leaf extract was given at a 300 mg/kg dose 2 h before the operation. Antioxidant enzyme activities and biochemical parameters were examined from the tissue and serum. Histopathological findings of the liver were scored semiquantitatively. RESULTS: Antioxidant enzyme activities in the artichoke leaf extract group were statistically significantly higher than that in the other two groups. Biochemical parameters, which show hepatocellular damage, were found to be similar in both sham and artichoke leaf extract groups. Although the values in the sham group were higher than the artichoke group in terms of protein and gene expressions, no statistically significant difference was found between these two groups. Regarding the hepatocellular effects of obstructive jaundice, the artichoke leaf extract group showed lower scores than the control group in all histopathological scores. CONCLUSION: The results of this study showed that artichoke leaf extract had a hepatoprotective effect that was associated with the antioxidant and anti-inflammatory effects of artichoke leaf extract.